2009
DOI: 10.1021/nn900022p
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray Ion Beam Deposition: Soft-Landing and Fragmentation of Functional Molecules at Solid Surfaces

Abstract: The ion beam deposition (IBD) of rhodamine dye molecules on solid surfaces in high vacuum is explored in order to characterize the possibility of fabricating molecular coatings or nanostructures from nonvolatile molecules. Molecular ion beams with a well-defined composition are deposited on silicon oxide surfaces with a controlled kinetic energy. Photoluminescence spectroscopy and time-of-flight secondary ion mass spectrometry (TOF-SIMS) are employed in order to characterize the sample with respect to coverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
116
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(123 citation statements)
references
References 56 publications
4
116
0
3
Order By: Relevance
“…32,33,34 Current developments of adapted electrospray and soft-landing techniques now permit the transfer of essentially any molecule or salt from solution to UHV. 35,36,37,38,39 d) The spatial resolution of UHV-STM (and now NC-AFM) is much higher than in solution, allowing precise characterization of sub-atomic details and conformations and precise measurements of interatomic distances. STM manipulation of single atoms and molecules is now a routine and precise technique that allows perturbation of the observed system to evaluate its stability and to displace molecules.…”
Section: Vacuum-solid Versus Liquid-solid Interfacesmentioning
confidence: 99%
“…32,33,34 Current developments of adapted electrospray and soft-landing techniques now permit the transfer of essentially any molecule or salt from solution to UHV. 35,36,37,38,39 d) The spatial resolution of UHV-STM (and now NC-AFM) is much higher than in solution, allowing precise characterization of sub-atomic details and conformations and precise measurements of interatomic distances. STM manipulation of single atoms and molecules is now a routine and precise technique that allows perturbation of the observed system to evaluate its stability and to displace molecules.…”
Section: Vacuum-solid Versus Liquid-solid Interfacesmentioning
confidence: 99%
“…with more conformational flexibility, is less well studied, for example the bending of chains on a surface. [14][15][16][17] This is mainly due to the difficulties in depositing such large molecules on surfaces in a clean and intact fashion, 18 and hence alternative strategies such as the on-surface formation of organometallic [19][20][21] or covalently bonded structures 22 are utilized. Although the adsorption geometry of monomers within a Cucoordinated polymer has been studied, 23 no details of the manipulation of the conformational structure of a molecular chain or the interaction between the conformation of the chain and its overall shape has been reported upon.…”
Section: Introductionmentioning
confidence: 99%
“…1) on an Au(111) surface with coverages ranging from submonolayer to multilayers. It has recently been shown that UHV-ESD and related spray techniques provide a viable method for the transfer of non-volatile/thermally labile species such as dye molecules and polymers from solution onto surfaces held in UHV [33][34][35][36][37][38][39] ; the development and application of this technique is crucial for the deposition of Mn 12 (acetate) 16 . Images of the adsorbed Mn 12 (acetate) 16 are acquired using an STM operating at room temperature under UHV conditions.…”
mentioning
confidence: 99%